INVESTIGATION OF X-RAY SYMMETRIC BBB-INTERFEROMETERS - Rostomyan, A. M. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
Different versions of X-ray symmetric interferometers with Bragg reflections are investigated. These interferometers with beam splitter, reflecting mirrors and analyzer are constructed from monolithic Si crystal. Versions of symmetric BBB-interferometers with optimal lamella thickness are calculated and experimentally tested.